Creative conflict resolution in collaborative editing systems - Sun, David (2013)
Conflict is common in collaboration, and may have both negative and positive effects on collaborative work. Past research has focused on controlling negative aspects of conflict by preventing, eliminating or isolating conflicts, but done little on exploring positive aspects of conflict. In this paper, we contribute a novel creative conflict resolution (CCR) approach to address these issues in real-time collaborative editing systems. In addition to maintaining consistency, the CCR approach is able to create new results from conflicts, generate alternative solutions based on collective effects of conflict operations, and support users to choose suitable conflict solutions and conflict resolution policies according to their needs. The CCR approach provides not only a new way of resolving conflicts in real-time collaborative editing systems, but also a framework for supporting a range of existing conflict resolution strategies. Techniques and user interface issues related to the CCR approach and a prototype implementation are discussed in this paper.